Behavioral Implications of Enrichment for Golden Lion Tamarins: A Tool for Ex Situ Conservation. Issue 3 (3rd July 2022) - Sanders, Kimberly; Fernandez, Eduardo J.
ABSTRACT: The re-release of golden lion tamarins ( Leontopithecus rosalia ), from zoos into the wild, is considered to be an  ex situ  conservation success story. However, zoo-born golden lion tamarins have lower survival rates than their wild-born offspring, potentially due to deficient foraging and locomotion 'survival skills' acquired in captivity. The current study aimed to evaluate whether a puzzle feeder suspended and baited with different items could promote increased foraging and general activity in tamarins living in a zoo setting. A pair of tamarins at Woodland Park Zoo received the puzzle feeder in three conditions in an ABCACB experimental reversal design over a period of three months: an empty feeder and feeders baited with either fruit (raisins) or insects (mealworms). Food type affected behavior; time spent climbing increased when the feeder contained insects compared to fruit. Subjects interacted with the baited puzzle feeder device significantly more than the empty feeder, and use was highest within the first 30 minutes of exposure. Our results suggest that the puzzle feeders plus food were effective in increasing foraging and general activity.